Prevalence of physical inactivity in Aligarh: scope for primary prevention - Ahamed, R; Ansari, A; Siddiqui, AR; Amir, A (Indian Journal of Community Health, 2013)
Background: Physical Inactivity is an important risk factor for non-communicable diseases accounting for 2 million deaths per year worldwide. Knowledge of prevalence of physical inactivity in different populations is limited. Methods: The present community based study was conducted in the field practice areas of the Urban Health Training Centre (UHTC) and Rural Health Training Centre (RHTC), Department of Community Medicine, Jawaharlal Nehru Medical College, Aligarh Muslim University, Aligarh, Uttar Pradesh, India. Systemic random sampling to include subjects was used. Six hundred and forty subjects were chosen for the study. The study was carried out for one year. Data were analyzed with SPSS version 13. Percentages and Chi Square Test used. Objective was to study the prevalence of physical inactivity and its sociodemographic correlates in rural and urban areas of Aligarh, UP. Results: The overall prevalence of work related physical inactivity and leisure time physical inactivity was 32% and 80.6% respectively. The prevalence of physical inactivity showed a significantly increasing trend with increasing age in both males and females. The physical inactivity related to work and leisure time was more in rural than urban areas and directly proportional to income and social class of the subjects. Conclusion: Physical inactivity has emerged as a fairly important risk factor and associated with all the age groups. Major ‘at risk’ groups are higher age groups and those belonging to higher socio economic strata.